Rearing conditions in domestic feline as a risk factor for Toxoplasma gondii infection - Castillo V., Lisset (2012)
The objective of the study was to quantify Toxoplasma gondii infections associated to rearing conditions in domestic cats: Controlled (at home) and Uncontrolled (access outside the house). It was collected 106 blood samples from various districts of Lima, and samples were analyzed by the Indirect Haemagglutination test (IHA). The risk factor to acquire T. gondii infection showed an Odds Ratio of 1.2 (0.47 - 3.5). No significant association was found between the frequency of infection and the type of rearing, but variables sex and diet were significantly associated (p<0.05). The study showed that T. gondii infections in domestic cats cannot be entirely attributed to the type of rearing conditions and that other sources of infection have to be taken into account to avoid the risk of infection of these animals and humans.